2012
DOI: 10.1002/ajpa.22160
|View full text |Cite
|
Sign up to set email alerts
|

The obstetric dilemma: An ancient game of Russian roulette, or a variable dilemma sensitive to ecology?

Abstract: The difficult birth process of humans, often described as the ''obstetric dilemma,'' is commonly assumed to reflect antagonistic selective pressures favoring neonatal encephalization and maternal bipedal locomotion. However, cephalo-pelvic disproportion is not exclusive to humans, and is present in some primate species of smaller body size. The fossil record indicates mosaic evolution of the obstetric dilemma, involving a number of different evolutionary processes, and it appears to have shifted in magnitude b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
237
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(261 citation statements)
references
References 295 publications
(397 reference statements)
22
237
0
2
Order By: Relevance
“…Pelvic dimensions have recently been shown to carry phylogenetic information relevant to human population history (Betti et al 2012(Betti et al , 2013; however, we know very little about the mechanisms controlling other skeletal dimensions. Pelvic dimensions, for example, may vary with ecological parameters, diet, and other aspects of phenotype (Wells et al 2012). In addition, lower limb length, in particular, the dimensions of the tibia, appears to be relatively sensitive to environmental variation (Trinkaus 1981;Holliday 1997;Stock 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic dimensions have recently been shown to carry phylogenetic information relevant to human population history (Betti et al 2012(Betti et al , 2013; however, we know very little about the mechanisms controlling other skeletal dimensions. Pelvic dimensions, for example, may vary with ecological parameters, diet, and other aspects of phenotype (Wells et al 2012). In addition, lower limb length, in particular, the dimensions of the tibia, appears to be relatively sensitive to environmental variation (Trinkaus 1981;Holliday 1997;Stock 2012).…”
Section: Discussionmentioning
confidence: 99%
“…africanus had a 'human-like movement of rotation and flexion of the fetal skull' during birth ( [56], p. 262; see also [36,75]). Neonatal head size relative to the size of the birth canal in australopithecines was probably closer to apes than humans ( [33,75 -77]; but see [1,36]), and the M -L wide and A-P narrow pelvis is seen by most authors as a barrier to birth of infants with relatively large brains (see [16] for a review of encephalization and birth in fossil hominins).…”
Section: Pelvic Evolution In Early (Non-homo) Homininsmentioning
confidence: 99%
“…Adult body size in H. heidelbergensis and the Neanderthals, which was within or above the modern human range, changed little during the Middle Pleistocene, but adult brain size did increase [24,60,74,113,114,116]. Fossil evidence suggests that Neanderthal infants were born with a body and head size similar to modern newborns, implying a similar level of obstetric difficulty in Neanderthals and modern humans [1,16,74,77,124] and probably 'obligate midwifery' (cf. [35,130]).…”
Section: (B) Middle Pleistocene Homomentioning
confidence: 99%
“…However, a recent study showed that neonatal size and human gestation length are limited not only by pelvic dimensions but also by maternal metabolic capacity (16). Phenotypic plasticity of pelvic dimensions and head size in response to changes in nutrition, poor food availability, and infectious disease burden, among others, might influence the severity of the obstetric dilemma (17)(18)(19).…”
mentioning
confidence: 99%